Fluorescent labelled thiourea-bridged glycodendrons - Krist, Pavel; Vannucci, Luca; Kuzma, Marek; Man, Petr; Sadalapure, Kashinath; Patel, Anupama; Bezouska, Karel; Pospísil, Milan; Petrus, Ladislav; Lindhorst, Thisbe K; Kren, Vladimír (Chembiochem, 2004)
GlcNAc-coated glycodendrimers, which are polyvalent glycomimetics, display strong in vitro affinity for the rat natural killer cell protein-1A (NKR-P1A), a C-type lectin-like receptor of natural killer (NK) cells in rats, humans and some strains of mice. Administration of these compounds in vivo results in a substantial increase in the antitumour activity with involvement of the natural cell immunity. To clarify the in vitro and in vivo fate of these molecules, we synthesized labelled glycodendron analogues of the previously studied glycodendrimers. Labelling with fluorescent tags enabled the localization of the glycodendrons in white blood cells, tumours and other tissues by using different imaging techniques such as fluorescence and confocal microscopy. These studies are useful for probing the mechanism of action and fate of artificial ligands and the cell receptors involved.
Keywords: Galactose; galaktosa; Killer Cells, Natural; Fluorescence; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; Glycoconjugates; Microscopy, Confocal; Mice; fluorescence; konfokální mikroskopie; slezina; glykokonjugáty; Thiourea; zvířata; myši; molekulární struktura; thiomočovina; buňky NK; Spleen; Molecular Structure; Animals